Teaching and Learning International Survey (TALIS) 2018: A Descriptive Analysis of Teacher Professional Development (TPD) in Indonesia - Suhandoko, Astri Dwi Jayanti; Rahayu, Ucu; Aisyah, Siti; Andayani, Andayani; Mikaresti, Pamela (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2024)
The Teacher Professional Development (TPD) program is a crucial strategy for enhancing teachers' knowledge and skills. The program includes activities that go beyond introducing instructional methods in the classroom and focus on improving teachers' abilities to communicate and collaborate with their peers, community of teachers, leaders, and school partners. There is a scarcity of research presenting TPD data from teacher representatives throughout Indonesia, particularly those using the 2018 TALIS questionnaire developed by the OECD. This mixed-method study collected TPD data from a survey of 410 elementary school teachers in Indonesia and interview data through the FGD method from 53 respondents, including teachers, principals, parent committees, and education offices from several cities in Indonesia. The study's results indicate that TPD programs in Indonesia require improvement and equal implementation both teachers in urban and suburban/rural area. The programs primarily focus on enhancing knowledge, instructional and institutional skills, including organic relationships with peers and school partners. Descriptive data analysis reveals that TPD programs should encourage cooperation and collaboration among teachers at local, national, and international levels. Recommendations for future research should analyze the effect of the TPD program integrated with the Merdeka Curriculum on teachers' committees. This will provide valuable insights into the effectiveness of the program.